Buddhayana: Tradisi Agama Buddha Yang Membawa Kesatuan Dalam Kebhinekaan Indonesia - lestari, tri; Nadia, Nadia; Andriyaningsih, Ayu; Sumarwan, Edi; Sutiyono, Sutiyono (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2023)
Buddhayana is a form of Buddhism adapted and accepted in a unique way in Indonesia. Buddhayana has become a symbol of harmony, unity and non-sectarianism in a pluralistic society. This research examines Buddhayana as a Buddhist tradition that has intersectarian, inclusivism and plurarism values that are in line with the value of diversity. The approach used in this research is qualitative with a literature review method through the search for primary and secondary information from various sources of books, articles, and the internet. The results of the study show that Buddhayana has successfully integrated local elements in its religious traditions, creating a unique form of Buddhism that suits the Indonesian social and cultural environment. This has been a positive contribution to interfaith harmony in Indonesia, providing a positive example of how different faiths can coexist peacefully. Buddhayana reinforces the notion of Indonesian diversity, reminding us of the importance of diverse religious cultures. Therefore, it is important to continue promoting the values of non-sectarianism and harmony so that Buddhayana and other religions remain agents of diversity in Indonesia. Buddhism in Indonesia is a successful example of interfaith harmony and religious adaptability in cultural diversity. Hopefully, the results of this research help to understand and appreciate the role of Buddhism in maintaining diversity and interfaith harmony in Indonesia and offer valuable insights into future challenges and opportunities